2021
DOI: 10.3847/1538-4357/abfd30
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale Magnetic Flux Ropes with Field-aligned Flows via the PSP In Situ Observations

Abstract: Magnetic flux rope, formed by the helical magnetic field lines, can sometimes maintain its shape while carrying significant plasma flow that is aligned with the local magnetic field. We report the existence of such structures and static flux ropes by applying the Grad-Shafranov-based algorithm to the Parker Solar Probe in situ measurements in the first five encounters. These structures are detected at heliocentric distances, ranging from 0.13 to 0.66 au, in a 4-month time period. We find that flux ropes with f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 39 publications
0
30
1
Order By: Relevance
“…Finally, it is noteworthy that a large number of nonforce‐free flux ropes in the solar wind have recently been identified (Chen et al., 2019, 2021). Particle‐in‐cell simulations by Lu et al.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it is noteworthy that a large number of nonforce‐free flux ropes in the solar wind have recently been identified (Chen et al., 2019, 2021). Particle‐in‐cell simulations by Lu et al.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Finally, it is noteworthy that a large number of nonforce-free flux ropes in the solar wind have recently been identified (Chen et al, 2019(Chen et al, , 2021. Particle-in-cell simulations by Lu et al (2021) indicated that force-free and nonforce-free flux ropes have different particle energization processes.…”
Section: Tablementioning
confidence: 98%
See 1 more Smart Citation
“…Magnetic flux ropes/islands are of a helical magnetic field structure for which the twist of magnetic field lines increases with increasing distance from the flux rope center. These twisted field structures are a by-product of magnetic reconnection, ranging in durations from a few minutes up to a few days in the solar wind (e.g., Burlaga 1988;Lepping et al 1990;Cartwright & Moldwin 2008;Gosling et al 2010;Feng et al 2015;Chen & Hu 2020, 2022Chen et al 2021), while in the Earth's magnetosphere from a few seconds to a few minutes (e.g., Slavin et al 2003;Teh et al 2010Teh et al , 2014aTeh et al , 2014bTeh et al , 2017Eastwood et al 2016;Wang et al 2016). A typical magnetic flux rope has a significant axial/core field that is increased largely at the center of the flux rope where the magnetic field strength is therefore significantly enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the extended GS equations by Sonnerup et al (2006) are different from those by Teh (2018Teh ( , 2019 under the same assumptions because the entropy equation and the double-polytropic energy laws (Hau & Sonnerup 1993) are used in the derivation of Sonnerup et al (2006). Recently, Chen et al (2021) and Chen & Hu (2022) have implemented an automated detection based on the extended GS equation by Teh (2018) to identify a large data set of small-scale magnetic flux ropes observed by the Parker Solar Probe in the solar wind. Moreover, the extended GS reconstruction with pressure anisotropy (Teh 2019) was applied for examining the geometry of mirror structures observed in the Earth's magnetosheath (Teh 2019) and the time-dependent mirror structure from double-polytropic MHD simulation (Teh & Zenitani 2021).…”
Section: Introductionmentioning
confidence: 99%